NILAI PENDIDIKAN KARAKTER DALAM FILM LAYANGAN PUTUS 1A PRODUKSI MD ENTERTAINMENT - Nurhuda, Abid (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Education aims to develop and change human beings to have good character and lead to perfection. However, along with the times and the entry of globalization, education conditions are increasingly vulnerable to changes in behavior that lead to moral degradation, so it is necessary to instill character education values as early as possible. It doesn't have to be focused on family, school, and society, but can also be done through other educational media such as films which have their charm for the audience. One of them is the Film Layangan Putus, and this study aims to describe what character education values are contained in the Film Layangan Putus episode 1A produced by MD Entertainment. The method used is a literature study with primary data, namely Film Layangan Putus episode 1A. In contrast, the secondary data are books, articles, and related journals accompanied by documentary techniques during collection, analyzed the contents and finally concluded. The result is that the values of character education in the Film Layangan Putus episode 1A produced by MD Entertainment include the importance of rationality, integrity, courage, humility, compassion, curiosity, democracy, religion, responsibility, independence, logical thinking, hard work, and wisdom.